Evidence for e(+)e(-) -> gamma eta(c)(1S) at center-of-mass energies between 4.01 and 4.60 GeV - Çetin, Serkant Ali (AMER PHYSICAL SOC, 2017)
We present first evidence for the process e(+)e(-) -> gamma eta(c)(1S) at six center-of-mass energies between 4.01 and 4.60 GeV using data collected by the BESIII experiment operating at BEPCII. We measure the Born cross section at each energy using a combination of twelve eta(c)(1S) decay channels. We also combine all six energies under various assumptions for the energy-dependence of the cross section. If the process is assumed to proceed via the Y(4260), we measure a peak Born cross section sigma(peak)(e(+)e(-) -> gamma eta(c)(1S)) = 2.11 +/- 0.49 (stat.) +/- 0.36 (syst.) pb with a statistical significance of 4.2 sigma.